Pharmacokinetics and Tolerance of the Natural Pentasaccharide (SR90107/ORG31540) with High Affinity to Antithrombin III in Man - Boneu, B; Necciari, J; Cariou, R; Sié, P; Gabaig, A M; Kieffer, G; Dickinson, J; Lamond, G; Moelker, H; Mant, T; Magnani, H (Thrombosis and Haemostasis, 1995)
This paper reports the results of the first administration of the synthetic natural pentasaccharide with high affinity to antithrombin III (NP) in man. The study was mainly focused upon the pharmacokinetic properties and general tolerance of the compound. Subcutaneous injections of doses <1.43 mg (1000 anti Xa IU) did not generate measurable anti-Xa activities. After subcutaneous injection of increasing doses from 1.43 to 22.9 mg (1000 to 16000 anti-Xa IU) to young healthy volunteers, it was found that the maximal concentration (Cmax) and the area under curve (AUC) were linearly correlated to the dose, that the total plasma clearances (Cl) were constant and almost 3 times lower than those of the current low molecular weight heparins. Cmax were reached between 1 h and 3 h after the injection and the half-lives (t1/2) were remarkably constant (13.1 h to 13.9 h). During the first 24 h following the injection, around 50% of the total administered dose was recovered in the urine in an active form, indicating that kidney plays a major role in the elimination of NP. Consistent with these results, when NP was administered to healthy elderly volunteers having a lower creatinine clearance, the half-life of the compound was longer and the clearance lower. At doses exceeding 22.9 mg, Cmax, and AUC were slightly lower than expected, the percentage of the dose recovered in the urine and the total apparent plasma clearance increased, suggesting that the excess of NP unbound to antithrombin III was excreted faster. NP was also administered at various dosages once or twice a day for 7 days to 20 elderly volunteers. Due to the long half-life of the compound the “steady state” was obtained 2 to 3 days after the first injection at which the mean Cmax was increased 1.5 to 2 times. The general tolerance of the compound was excellent. No relevant prolongations of the prothrombin time, of the activated partial thromboplastin time or of the bleeding time were observed. A re-bleeding phenomenon of the bleeding time incision, probably related to friability of the haemostatic plug, occurred in 3 subjects treated with the highest dose regimens: single injection of 26.6 mg (20000 anti-Xa IU) (young volunteers) and repeated injections of 11.4 mg (8000 anti-XaIU) once a day for 7 days (elderly volunteers). At these times, plasma NP concentrations were between 2.9 and 3.6 μg ⋅ ml-1 (2 and 2.5 anti-Xa IU ⋅ ml-1).